DEVELOPMENT AND EVALUATION OF A NOVEL TIME AND PH-DEPENDENT COLON TARGETED DRUG DELIVERY OF ORNIDAZOLE - M, SUSHMA; S, PAVANI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The anti-amoebic drug Ornidazole was developed in this study as a novel colon-specific drug delivery method for the treatment of colonic diseases such as diverticulitis, inflammatory bowel syndrome, and Crohn’s disease. Pectin forms a matrix with a pH-sensitive polymeric coating that prevents drug release in the upper gastrointestinal tract, thereby addressing solubility issues. Pectin is sometimes used as an adsorbent, bulk-forming agent. Methods: Ornidazole-containing core tablets were directly compressed. Ornidazole compression coated tablets were formulated with varying polymer proportions in the coat. All the tablets were studied for weight uniformity, hardness, friability, drug content, and in vitro dissolution tests Results: All formulations demonstrated good Fourier-transform infrared compliance and no interaction between drug, polymer, and other excipients. The study’s findings show that the formulation F6 coated with Eudragit RS 100 had a drug release of 99.230.8 for 24 h. Conclusion: As a result, (F6) is regarded as the optimal formulation. The pH in the colon causes the release of Ornidazole from tablets.